Introducing Extended Data on Terrorist Groups (EDTG), 1970 to 2016 - Hou, Dongfang (2020)
This article introduces an extended data set of 760 terrorist groups that engaged in attacks during 1970 to 2016. Unlike most extant group data sets, the extended data on terrorist groups (EDTG) is not tied to terrorist groups and attacks listed in the RAND terrorism data; rather, EDTG is linked to terrorist groups and attacks given in the Global Terrorism Database. Terrorist groups’ variables in EDTG include ideology, main goals, start date, duration, base country, attack diversity, peak size, alternative endings (if relevant), and others. We display interesting features of EDTG through a series of tables and figures. Our EDTG-based survival analysis is at odds with some of the literature: for example, the demise of a leader and a larger share of transnational terrorist attacks increase the group’s odds of failure. After 2001, religious terrorist groups are more resilient than those with other ideologies. We also analyze terrorist group lethality and productivity.